2016
DOI: 10.1080/02664763.2016.1191624
|View full text |Cite
|
Sign up to set email alerts
|

Negative variance components for non-negative hierarchical data with correlation, over-, and/or underdispersion

Abstract: The concept of negative variance components in linear mixed-effects models, while confusing at first sight, has received considerable attention in the literature, for well over half a century, following the early work of Chernoff [7] and Nelder [21]. Broadly, negative variance components in linear mixed models are allowable if inferences are restricted to the implied marginal model. When a hierarchical view-point is adopted, in the sense that outcomes are specified conditionally upon random effects, the varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Although a few researchers have reported about negative clustering effects (El Leithy et al, 2016;Kenny et al, 2002;Klotzke & Fox, 2019a, 2019bLoeys & Molenberghs, 2013;Molenberghs & Verbeke, 2007Oliveira et al, 2017;Pryseley et al, 2011;Verbeke & Molenberghs, 2003), the effects of ignoring negatively clustered observations has hardly been recognized. Because negative clustering effects are not considered by the majority of the multilevel modelling community, these effects are not well understood.…”
Section: Type-i Errors and Positive And Negative Dependencies Betweenmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a few researchers have reported about negative clustering effects (El Leithy et al, 2016;Kenny et al, 2002;Klotzke & Fox, 2019a, 2019bLoeys & Molenberghs, 2013;Molenberghs & Verbeke, 2007Oliveira et al, 2017;Pryseley et al, 2011;Verbeke & Molenberghs, 2003), the effects of ignoring negatively clustered observations has hardly been recognized. Because negative clustering effects are not considered by the majority of the multilevel modelling community, these effects are not well understood.…”
Section: Type-i Errors and Positive And Negative Dependencies Betweenmentioning
confidence: 99%
“…However, when modeling the covariance structure with the LME, the τ is restricted to be greater than zero, since it represents the random intercept variance. In the literature, it has been shown that the maximum likelihood estimate of the random effect variance can become negative (El Leithy et al, 2016;Kenny et al, 2002;Klotzke & Fox, 2019a, 2019bLoeys & Molenberghs, 2013;Molenberghs & Verbeke, 2007Oliveira et al, 2017;Pryseley et al, 2011;Verbeke & Molenberghs, 2003). For the (oneway) LME (for balanced groups), two sums of squares are considered to estimate the covariance components τ and σ 2 ,…”
Section: The Linear Mixed Effects Model With Negative Variance Componmentioning
confidence: 99%
See 3 more Smart Citations